Identifying structural similarities between stricto sensu post-graduation programs in management regarding the strategy tripod (REGE Revista de Gestão, 2018)
Purpose – The purpose of this paper is to identify the structural similarities between stricto sensu post-graduation programs in management through the formation of clusters, with the strategy tripod as a backdrop (Peng, 2002; Peng et al., 2009). Design/methodology/approach – The co-plot method was used as a tool. It was chosen because it simultaneously enables joint and individual observations of comments and variables. Findings – The results showed the formation of clusters among the programs, identifying a series of similarities between their components. The age and number of lines of research of the programs were the determining variables to identify isomorphism among the clusters. Research limitations/implications – The main limitation of the study lies in the updating of information at the source of the data collection. All the data were collected from the Sucupira Platform for CAPES Triennial Evaluation of 2013. However, when the authors accessed the portals of the programs, the authors found that some data were outdated. Nevertheless, the authors limited themselves to using official data. Therefore, even if the authors found divergences or inconsistencies regarding the published information, the authors decided to use the official data made available by CAPES on the Sucupira Platform for the period in question. Originality/value – Understanding that the results through the approaches of the industry-based view, resource-based view and institution-based view were insufficient for a thorough analysis, it is demonstrated in isolation that none of these succeeds in explaining the organizational context that permeates Brazilian stricto sensu post-graduation institutions. In this organizational field, the three views are not at the same theoretical level. The institutional view overlaps with the strategic competitive views. Therefore, the study contributes to reorganizing the strategy tripod and the proposed articulation between the arrangement of theory, method and field research.